Measurement uncertainty analysis of leak localisation in a gas pipeline. (December 2021) - Chen, Runchang; Cui, Shan; Khoo, David Wee Yang; Khoo, Boo Cheong
Abstract: Leak location in a gas pipeline can be estimated by negative pressure wave method. To evaluate the accuracy of the estimated leak location, measurement uncertainty (MU) must be studied and accounted for. A model has been introduced to calculate the MU of the estimated leak location according to the Guide to the Expression of Uncertainty in Measurement together with Monte Carlo method. Firstly, it is noted that the manual measurement process of pipeline length and actual leak locations has substantial contribution to the MU. Secondly, when a leak is closer to one end of the pipeline, the localisation MU is affected more by the temperature and flow MUs at the other end of the pipeline. Finally, the expanded MU increases as the leak location moves further away from the pipeline inlet, ranging from 0.0522% to 0.0806% mainly due to the manual dimensional measurement.